Networking reviewed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Information exchange networking for agricultural development by John Nelson and John Farrington 994 86pp ISBN 92 9081 1137 Available from CTA